ECONOMIC ANALYSIS OF THE ROLE OF AGRICULTURAL PRODUCTION IN MEETING THE DEFENSE NEEDS OF THE REPUBLIC OF SERBIA - Mihajlović, Milan; Milunović, Milan; Ćearmilac, Uroš (Economics of Agriculture, 2024)
The comprehensive influence and importance of agricultural production on the economy of the Republic of Serbia and its connection with the defense system represent an interesting research topic. This topic has to be researched carefully due to the connection, mutual influence, and mutual intertwining of commodity reserves of food products, the economic system, the defense system, and the army as one of its components, with social and political factors, both internal and external. Since the beginning of the COVID-19 pandemic, global increases in food prices have been noticeable. This problem arose with the beginning of the conflict in Ukraine. It should be understood that the commodity reserve system of food products is a subsystem within a series of higher subsystems and systems, and that this is where its complexity and comprehensiveness lie.